Long‐noncoding RNA Atrolnc‐1 promotes muscle wasting in mice with chronic kidney disease. Issue 5 (24th July 2018) - Sun, Lijing; Si, Meijun; Liu, Xinyan; Choi, Jong Min; Wang, Yanlin; Thomas, Sandhya S.; Peng, Hui; Hu, Zhaoyong
Abstract: Background: Chronic kidney disease (CKD) is commonly associated with cachexia, a condition that causes skeletal muscle wasting and an unfavourable prognosis. Although mechanisms leading to cachexia have been intensively studied, the advance of biological knowledges and technologies encourages us to make progress in understanding the pathogenesis of this disorder. Long noncoding RNAs (lncRNAs) are defined as >200 nucleotides RNAs but lack the protein‐coding potential. LncRNAs are involved in the pathogenesis of many diseases, but whether they functionally involve in muscle protein loss has not been investigated. Methods: We performed lncRNA array and identified an lncRNA, which we named Atrolnc‐1, remarkably elevated in atrophying muscles from mice with cachexia. We examined how overexpression or knockdown of Atrolnc‐1 could influence muscle protein synthesis and degradation. We also examined whether inhibition of Atrolnc‐1 ameliorates muscle wasting in mice with CKD. Results: We documented that Atrolnc‐1 expression is continuously increased in muscles of mice with fasting (5.4 fold), cancer (2.0 fold), or CKD (5.1 fold). We found that depressed insulin signalling stimulates the transcription factor C/EBP‐α binding to the promoter of Atrolnc‐1 and promotes the expression of Atrolnc‐1. In cultured C2C12 myotubes, overexpression of Atrolnc‐1 increases protein degradation (0.45±0.03 vs. 0.64±0.02, *p<0.05); Atrolnc‐1 knockdown significantly reduces the rate of protein degradation stimulated by serum depletion (0.61±0.03 vs. 0.47±0.02, *p<0.05). Using mass spectrometry and a lncRNA pull‐down assay, we identified that Atrolnc‐1 interacts with A20 binding inhibitor of NF‐κB‐1 (ABIN‐1). The interaction impairs function, resulting in enhanced NF‐κB activity plus MuRF‐1 transcription. This response is counteracted by CRISPR/dCas9 mediated overexpression. In muscles from normal mice, overexpression of Atrolnc‐1 stimulates a 2.7‐fold increase in MuRF‐1 expression leading to myofibers atrophy. In contrast, Atrolnc‐1 knockdown attenuates muscle wasting by 42% in mice with CKD via suppression of NF‐κB activity and MuRF‐1 expression. Conclusions: Our findings provide evidence that lncRNAs initiates the pathophysiological process of muscle wasting. The interaction between Atrolnc‐1 and NF‐κB signalling modulates muscle mass and proteolysis in CKD and perhaps other catabolic conditions.